2019
DOI: 10.1080/16078055.2019.1636857
|View full text |Cite
|
Sign up to set email alerts
|

“Magic Mirror on the Wall”: is Nordic walking or rambling better for your mental well-being?

Abstract: There is accumulating evidence that walking has health benefits. While millions of people in the United Kingdom have long benefitted from rambling, Nordic walking is a relative newcomer to the shores of Britain. Which of these forms of walking is better for your mental wellbeing? This study set out to compare both forms of walking and measured their effects on mental wellbeing using the Warwick Edinburgh Mental Well-being Scale (WEMWBS), through an online survey. In addition both groups of walkers were asked a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Extending this provision, as more organizations and individuals discover the positive influence adaptive sport and adventure training can have, even beyond that of exercise alone, sporting contexts such as the Multi Activity Course (MAC) are now increasingly being provided for Veterans and recovering military personnel in the UK and around the world (Buckley et al, 2018 ). Such programs, using activities like surfing, river boarding, and hill walking, have been reported to have positive effects on participant well-being (Caddick & Smith, 2017 ; Dustin et al, 2011 ; Zurawik et al, 2019 ). This has been seen recreationally as well as at high-performance levels, including Invictus Games athletes (Roberts et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Extending this provision, as more organizations and individuals discover the positive influence adaptive sport and adventure training can have, even beyond that of exercise alone, sporting contexts such as the Multi Activity Course (MAC) are now increasingly being provided for Veterans and recovering military personnel in the UK and around the world (Buckley et al, 2018 ). Such programs, using activities like surfing, river boarding, and hill walking, have been reported to have positive effects on participant well-being (Caddick & Smith, 2017 ; Dustin et al, 2011 ; Zurawik et al, 2019 ). This has been seen recreationally as well as at high-performance levels, including Invictus Games athletes (Roberts et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fischer et al [20] reported a significant reduction in shoulder problems among women with breast cancer immediately after the Nordic walking intervention. In contrast, the psychological and social benefits of the activity have attracted recent attention, which is still very limited [21][22][23].…”
Section: Introductionmentioning
confidence: 99%